2020
DOI: 10.1101/2020.07.29.226977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclear and cytoplasmic huntingtin inclusions exhibit distinct biochemical composition, interactome and ultrastructural properties

Abstract: Despite the strong evidence linking the aggregation of the Huntingtin protein (Htt) to the pathogenesis of Huntington’s disease (HD), the mechanisms underlying Htt aggregation and neurodegeneration remain poorly understood. Herein, we investigated the ultrastructural properties and protein composition of Htt inclusions in cells overexpressing mutant exon1 of the Htt protein. Our findings provide novel insight into the ultrastructural properties of cytoplasmic and nuclear Htt inclusions and their mechanisms of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 209 publications
(385 reference statements)
2
26
0
Order By: Relevance
“…Similarly, the reduction in the number of cells with inclusions was much less pronounced after overexpression of the M8P-Httex1-GFP 72Q than M8P-Httex1 tag-free ( Figure 4B). This emphasizes our recent findings showing that the fusion of GFP proteins to Httex1 alters the structural and aggregation properties of the protein as well as its biological functions 52 .…”
Section: The Addition Of Gfp To the C-terminal Part Of Httex1 Stronglsupporting
confidence: 70%
See 3 more Smart Citations
“…Similarly, the reduction in the number of cells with inclusions was much less pronounced after overexpression of the M8P-Httex1-GFP 72Q than M8P-Httex1 tag-free ( Figure 4B). This emphasizes our recent findings showing that the fusion of GFP proteins to Httex1 alters the structural and aggregation properties of the protein as well as its biological functions 52 .…”
Section: The Addition Of Gfp To the C-terminal Part Of Httex1 Stronglsupporting
confidence: 70%
“…These effects were examined in the context of Httex1 carrying polyQ tracts of various lengths (16Q, 39Q, or 72Q), which also allowed us to investigate the effect of the Nt17 domain as a function of increasing polyQ-repeat length. Given that recent studies from our group demonstrated that the addition of a GFP tag to the Httex1 72Q protein dramatically influenced the biochemical composition and ultrastructural properties of Httex1 inclusions 52 , we performed our studies using Httex1 or ΔNt17-Httex1 constructs with different polyQ-repeat lengths (16Q, 39Q, and 72Q, Figure S7A) and fused or not to GFP. The use of Httex1-GFP fusion proteins allows us to compare our findings to published studies, most of which are based on the use of mutant Httex1-GFP/YFP proteins [61][62][63][64][65][66][67][68][69][70] .…”
Section: The Helical Conformation Of the N17 Domain Is A Key Determinmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the disease-causing mHtt protein interacts with mitochondria and may specifically impair complex II [ 189 ]. mHtt has been demonstrated to induce mitochondrial fragmentation [ 190 ] and cytoplasmic inclusions of mHtt Exon1 have recently been shown to also recruit mitochondria and cause their fragmentation as well as mitochondrial respiratory abnormalities [ 191 ]. Hypoxic conditioning, on the other hand, may counteract mitochondrial fragmentation by enhancing mitochondrial fusion [ 192 ].…”
Section: Conditioning Benefits On Mitochondrial Dysfunctions Oxidmentioning
confidence: 99%